Pengembangan Usaha UMKM Catering Di Desa Dongos Untuk Meningkatkan Perekonomian Rumah Tangga - Afiq, Choirul; Nafi’ah, Annihayatun; Shofiyanah, Faisyatus; Sofiana, Nina (Jurnal Pengabdian kepada Masyarakat Khaira Ummah, 2023)
A good economy will have a positive impact on various aspects, such as health, education and the economy. The existence of UMKM in Dongos Village provides a great opportunity for employment for the community, and can be used as one of the Local Original Income Sources. The methods used in carrying out this activity are data collection techniques, training, product development and business licensing assistance. Community service activities in collaboration with "Rizki Barokah" partners UMKM include conducting marketing training activities, developing labels that have a function for promotion, and licensing assistance. From the community service activities that have been carried out, we hope that partners will be able to promote products online, partners will be able to increase consumer buying interest through labeled packaging so that they can compete with other UMKM. Apart from that, the existence of NIB is expected to facilitate the activities of business actors in Indonesia, to be able to increase investment and business.